2009
DOI: 10.1158/1055-9965.epi-09-0398
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Polymorphism rs1329149 of CYP2E1 and a Known Polymorphism rs671 of ALDH2 of Alcohol Metabolizing Enzymes Are Associated with Colorectal Cancer in a Southwestern Chinese Population

Abstract: Background: To screen for tagging single nucleotide polymorphisms (tagSNP) in the major alcohol metabolizing enzymes: ADH1B, ALDH2, and CYP2E1, and to evaluate the association between these tagSNPs and colorectal cancer (CRC) in a southwestern Chinese population. Methods: A hospital-based case-control study of 440 CRC patients and 800 cancer-free controls was conducted. Personal information was collected by a SemiQuantitative Food Frequency Questionnaire. The tagSNPs were screened in the HapMap with Haploview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 31 publications
5
53
2
Order By: Relevance
“…Gene rs671, rs1329149, age, and alcohol consumption correlate with the morbidity of colorectal cancer. Based on OR, all of these four factors are risk factors for the pathogenesis of colorectal cancer, which is consistent with results in the literature (Yang et al, 2009). Next, the interactions between these factors were analyzed by combining crossover analysis and logistic regression methods.…”
Section: Results Of Logistic Regression Analysissupporting
confidence: 83%
See 3 more Smart Citations
“…Gene rs671, rs1329149, age, and alcohol consumption correlate with the morbidity of colorectal cancer. Based on OR, all of these four factors are risk factors for the pathogenesis of colorectal cancer, which is consistent with results in the literature (Yang et al, 2009). Next, the interactions between these factors were analyzed by combining crossover analysis and logistic regression methods.…”
Section: Results Of Logistic Regression Analysissupporting
confidence: 83%
“…From biological view in the literature (Yang et al, 2009), the risk factors of colorectal cancer were analyzed by using chi-square test, the characteristics of related gene locus and environmental factors associated with the development of colorectal cancer were found. However, the interactions between these factors are not fully analyzed.…”
Section: Statistics Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…O 6 -methylguanine-DNA methyltransferase (MGMT) is involved in the direct damage-reversal pathway, which repairs damaged DNA and thus decreases cancer risk (Loh et al, 2011). Aldehyde dehydrogenase-2 (ADH1B) is a major enzyme involved in the alcohol-metabolizing pathways, and ADH1B can metabolize acetaldehyde into acetic acid for detoxification (Yang et al, 2009). Although a meta-analysis reported that ADH1B genetic polymorphisms can increase the risk of cancers of the upper aerodigestive tract, including the oral cavity, pharynx, larynx, and esophagus (Guo et al, 2012), there was a lack of summary for ADH1B variants in the susceptibility of CRC.…”
Section: Introductionmentioning
confidence: 99%